Digital holographic microscopy for the evaluation of human sperm structure. Issue 4 (November 2014) - Coppola, G.; Di Caprio, G.; Wilding, M.; Ferraro, P.; Esposito, G.; Di Matteo, L.; Dale, R.; Coppola, G.; Dale, B.
Summary The morphology of the sperm head has often been correlated with the outcome of in vitro fertilization, and has been shown to be the sole parameter in semen of value in predicting the success of intracytoplasmic sperm injection and intracytoplasmic morphologically selected sperm injection. In this paper, we have studied whether digital holographic microscopy (DHM) may be useful to obtain quantitative data on human sperm head structure and compared this technique with high-power digitally enhanced Nomarski optics. The main advantage of digital holography is that high-resolution three-dimensional quantitative sample imaging may be automatically produced by numerical refocusing of a two-dimensional image at different object planes without any mechanical scanning. We show that DHM generates useful information on the dimensions and structure of human sperm, not revealed by conventional phase-contrast microscopy, in particular the volume of vacuoles, and suggest its use as an additional prognostic tool in assisted reproduction technology.